An investigation on the flow and vortical structure of a pre-swirl stator pump-jet propulsor in drift. (15th April 2022) - Li, Han; Huang, Qiaogao; Pan, Guang; Dong, Xinguo; Li, Fuzheng
Abstract: Analysis of an underwater propulsor in different conditions is widely concerned in naval hydrodynamics due to the close connections with design and performance. Large lateral loads on a propulsor may be produced in drift, critical for bearing safety and maneuvering. This work aims to investigate the oblique flow effects (0°–30°) on a pre-swirl stator pump-jet propulsor (PJP). Numerical calculations are conducted by improved delayed detached eddy simulation. The results perform consistent with the experiment. The forces on the rotor, stator, and duct are discussed, focusing on the magnitude and fluctuation. Then the flow and its coherent structures are analyzed. Results indicate that the PJP has significant force fluctuation and more complex vortices evolution in drifts. The forces change considerably, and their fluctuations are aggravated and have more low-frequencies components. The duct has the hugest force change. The leeward of duct outside forms a considerable flow separation at high advance coefficients in high drift, breaking the PJP wake morphology. The duct separating vortices accelerates the interaction between the tip clearance leakage vortices and the duct shed vortices. The mainstream in the windward has a deflection to the leeward, and the interaction with freestream accelerates the vortex dissipation. The stator blades, whose pre-swirl directions are inverse with the cross-flow, occur considerable flow separations at high advance coefficients in drifts, forming considerable separating vortices successively interacting with wake vortices of the stator and rotor. Highlights: The thrust and its fluctuation characteristics of a PJP in drifts are investigated. The effects of drift angle on the PJP flow characteristics are discussed. The vortical structures and the underlying flow instability mechanism of a PJP in drifts are revealed.